If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3p + -4 = 2p Reorder the terms: -4 + -3p = 2p Solving -4 + -3p = 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -4 + -3p + -2p = 2p + -2p Combine like terms: -3p + -2p = -5p -4 + -5p = 2p + -2p Combine like terms: 2p + -2p = 0 -4 + -5p = 0 Add '4' to each side of the equation. -4 + 4 + -5p = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5p = 0 + 4 -5p = 0 + 4 Combine like terms: 0 + 4 = 4 -5p = 4 Divide each side by '-5'. p = -0.8 Simplifying p = -0.8
| a+3-4=-1 | | -5+13x=-6x^2 | | -9v=27 | | 48-(12)= | | 3(c-22)=2(c-6) | | r^2+2r-7=0 | | 3.7=.21w | | -12h+39=-4h-7 | | 12(4x-4)=4(12x+1) | | 40+15+0.25x=45+45+0.35x | | 8(x-6)+(-3x)=5(x-6)+3 | | 2h-35=2h+15 | | -8+4=5u-3u | | 4s-6=7s+3 | | (2x+1.5).15=11.5 | | 4.2+1.7x=2.7x | | 64n^2+36=0 | | 5(u-3)-7=-9+u-1 | | n/3=12 | | -2[5-(2z+1)]-4=2(3-2) | | 27x-3x^2=60 | | 8+5n-3=8n+11-5n | | -4(2x-6)= | | .15(2x+1.5)=11.50 | | 15x=-10x^2+10 | | -10+2x= | | -4(x+5)=2(x+5) | | P^2+4p+4=0 | | 4t-8-2y+5=0 | | 2x+(4x+150)=180 | | .015(2x+1.5)=11.5 | | 2t+9=-8t-13 |